Pulau Kemaro : Simbol Toleransi Antaragama di Sumatera Selatan - Fitria Marisya; Dwi Hanadya; Nyayu Ully Auliana; Sherly Malini; M. Bambang Purwanto (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This Community Service (PKM) activity aims to promote and strengthen the values of interreligious tolerance in South Sumatra through the introduction and preservation of Kemaro Island as a symbol of tolerance. Kemaro Island is a small island in the Musi River, Palembang, which is known for the legend of love between a Chinese prince and a princess of Palembang as well as the existence of Buddhist temples that are side by side with the traditions of the local community. Through a series of activities such as workshops, seminars, cultural exhibitions, and educational tours, the program engages various elements of society, including youth, religious leaders, and academics, to understand the history and cultural values of Kemaro Island. This activity also includes training for local tour guides to be able to convey accurate and interesting information about Kemaro Island to visitors. In addition, this program seeks to increase public awareness of the importance of maintaining and preserving cultural sites as valuable heritage. It is hoped that through this activity, the community can better appreciate cultural and religious diversity and foster a spirit of tolerance and harmony in daily life. The results of this PKM activity will be documented in the form of scientific reports and publications, and are expected to be a model for other regions in developing and promoting the values of tolerance through local cultural heritage.